Comparative analysis of neutropenia in patients receiving prolonged treatment with ceftaroline. (8th December 2017) - Turner, R Brigg; Wilson, D Erin; Saedi-Kwon, Henry; Chang, Eric; Won, Regina; Chan, Dominic; Schwartz, Jacqueline
Abstract: Objectives: Ceftaroline is often used in durations greater than that studied in clinical trials. Several retrospective, non-comparative studies have suggested a higher than anticipated incidence of neutropenia in patients receiving prolonged treatment with ceftaroline. We sought to determine if ceftaroline was associated with neutropenia by comparing the incidence with ceftaroline treatment with treatment with several comparative antibiotics. Methods: Patients receiving 14 or more consecutive days of treatment with ceftaroline were compared with patients receiving cefazolin, daptomycin, linezolid, nafcillin or vancomycin (control group). The primary outcome was the development of neutropenia. Multivariate logistic regression and propensity score weighting using inverse probability weights with regression adjustment were used to control for confounding variables. Results: A total of 753 patients were included (53 that received ceftaroline and 700 that received a comparative antibiotic). Ceftaroline was associated with a greater incidence of neutropenia as compared with the control group (17.0% versus 3.9%, P  < 0.001). Several covariates were also associated with neutropenia and included younger age, lower baseline absolute neutrophil count, liver disease and bone and joint infections. After controlling for these confounders, receipt of ceftaroline continued to be associated with the development of neutropenia (adjusted OR 3.97, P  =   0.003). Analysis after propensity score weighting confirmed this finding. Conclusions: The results of this study suggest that prolonged treatment with ceftaroline is associated with a greater incidence of neutropenia as compared with other antibiotics that are often used for treatment of staphylococcal infections. Careful monitoring of absolute neutrophil count is recommended in patients receiving >14 days of ceftaroline.